KAJIAN SPASIAL PERUBAHAN LAHAN TERHADAP PESEBARAN PEMUKIMAN DI KECAMATAN KEBAYORAN LAMA TAHUN 2004 SAMPAI 2024 - farah safira safira; Syairul Bahar; Andri Noor Ardiyansyah (Jurnal Geografi, 2026)
Population growth in Kebayoran Lama District has increased the need for land for settlements and economic activities, thus triggering changes in land use that have the potential to reduce non-built-up land. This study aims to analyze changes in land use and settlement distribution patterns in Kebayoran Lama District during the period 2004–2024. The method used is quantitative descriptive with a spatial-temporal approach based on Geographic Information Systems (GIS). The analysis of land use changes was carried out using an overlay technique of land use maps in 2004, 2014, and 2024, while the settlement distribution pattern in 2024 was analyzed using Average Nearest Neighbor (ANN). The results show that the settlement area increased from 652 ha to 1,294 ha, while mixed vegetation decreased from 947 ha to 333 ha and vacant land decreased from 189 ha to 7 ha. The ANN results show a Nearest Neighbor Ratio of 0.668 with a z-score of -10.293 and a p-value of 0.000, indicating a clustered settlement distribution pattern. This study recommends strengthening spatial use controls and protecting undeveloped land to maintain a balance between urban development and environmental sustainability.